The interpreter's Bible ; v. 9 the Holy Scriptures in the King James and Revised Standard versions with general articles and introduction, exegesis, exposition for each book of the Bible in twelve volumes. - Buttrick, George Arthur, 1892-1980 (Nashville, TN Abingdon, 1952)
Contents : v. 9 : Acts, Romans. Includes bibliographical references, maps.
Keywords: Bible -- commentaries